Persecution of Women in Afghanistan under International Criminal Law - Sabera Hussaini (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
This research analyzes the policies and actions of the Taliban against women and girls after 2021 and evaluates them within the framework of international criminal law, in particular, the gender-based persecution as a crime against humanity under Article 7 (1) (h) of the Rome Statute. The research design is qualitative, descriptive-analytical, and founded on legal-documentary approach, and data were collected from international legal documents, the jurisprudence of the International Criminal Court, reports of the United Nations, and the human rights organizations. The results of the research reveal that institutionalized policies of the a Taliban in the spheres of education, employment, healthcare, freedom of movement, and access to justice represent a harsh and premeditated deprivation of essential rights of an identifiable group of people on gender basis and include the legal components of crimes against humanity (harassment and persecution). According to the findings of the research, this has reached past being a human rights crisis and has become a prosecutable case in terms of the international criminal law.